A phase-shifted carrier-based PWM technique for cascaded h-bridge inverters application in standalone PV system - Boonmee C. (2015)
A phase-shifted carrier-based pulse width modulation strategy of two single-phase cascaded H-bridge inverters with separated solar photovoltaic sources, for standalone applications, is proposed in this paper. These functions are derived from a conventional unipolar modulation method with two phase-shifted triangular carrier waves, which can be easily implemented. The modulation strategy was developed to provide a five-level output waveform with a non unity power factor load. The possibility of the proposed technique has been verified though computer simulations and experimental results. © 2012 IEEE.